2019
DOI: 10.1093/molbev/msy232
|View full text |Cite
|
Sign up to set email alerts
|

A Single SNP Turns a Social Honey Bee (Apis mellifera) Worker into a Selfish Parasite

Abstract: The evolution of altruism in complex insect societies is arguably one of the major transitions in evolution and inclusive fitness theory plausibly explains why this is an evolutionary stable strategy. Yet, workers of the South African Cape honey bee ( Apis mellifera capensis ) can reverse to selfish behavior by becoming social parasites and parthenogenetically producing female offspring (thelytoky). Using a joint mapping and population genomics approach, in combination with a time-course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 87 publications
(146 reference statements)
1
38
0
1
Order By: Relevance
“…The long‐term breeding programme for high royal jelly producing honey bees in China has resulted in an extraordinary and stable social phenotype, enabling the entire royal jelly production industry and providing a unique opportunity for understanding female reproductive investment in social insects. The study of complex social phenotypes using selected strains has revealed underlying molecular changes in a few cases that involve individual reproductive physiology (Aumer et al, ; Page et al, ; Ronai et al, ), but the breadth and duration of the selection programme for high royal jelly production is unprecedented and has led to a novel social phenotype. The increased production of new queens and royal jelly (RJ) provisioning per queen correspond in >10‐fold higher RJ production of RJBs compared to unselected Italian (ITB) honey bees that the RJBs were originally derived from (Li & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term breeding programme for high royal jelly producing honey bees in China has resulted in an extraordinary and stable social phenotype, enabling the entire royal jelly production industry and providing a unique opportunity for understanding female reproductive investment in social insects. The study of complex social phenotypes using selected strains has revealed underlying molecular changes in a few cases that involve individual reproductive physiology (Aumer et al, ; Page et al, ; Ronai et al, ), but the breadth and duration of the selection programme for high royal jelly production is unprecedented and has led to a novel social phenotype. The increased production of new queens and royal jelly (RJ) provisioning per queen correspond in >10‐fold higher RJ production of RJBs compared to unselected Italian (ITB) honey bees that the RJBs were originally derived from (Li & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study within a single Capensis colony headed by a naturally mated queen identified a second candidate th locus on chromosome 1, GB46427 [35,36]. GB46427 is linked to Ecdysis-triggering hormone receptor (Ethr) within a non-recombining region of the genome [36].…”
Section: Introductionmentioning
confidence: 99%
“…Charting the genotype-phenotype map in honey bees has been substantially enhanced by the availability of a genome sequence because it allows powerful techniques such as the genomewide association mapping of complex traits Zayed 2019, Kent et al 2019;Grozinger and Zayed 2020). These approaches were recently applied to study the genetics of thelytoky yielding a different candidate gene on chromosome 1, GB46427 (Aumer et al 2017, Aumer et al 2019; this uncharacterized gene contains a non-synonymous single nucleotide mutation that was strongly associated with worker clonal reduction in a single Cape honey bee colony. Yet again, population genomic data refuted this hypothesis, as the thelytoky-associated mutation in GB46427 in Aumer et al's study was also common in non-thelytokous populations (Christmas et al 2019).…”
Section: Case Studies: What Happened When Honey Bee Genomics Was Applied To Fundamental Questions In Bee Biology and Health?mentioning
confidence: 99%